A influência do contexto na identidade dos personagens de Ensaio sobre a cegueira, de Saramago - Camargo, Amanda Kristensen de [UNESP] (2015)
This research aims to investigate the consequences of a possible change caused by the social context in the life and behavior of the main characters in the novel Blindness, [by José Saramago]. Starting by that there is an allegorical correlation between the blindness white, discussed by Saramago in his novel and the construction of the Plato's Cave Myth, and taking as theoretical basis the reflections of some thinkers such as Stuart Hall (1992), Goffman (2002) and Antonio da Costa Ciampa (2005) it be sought to describe the occurrence of the phenomenon the social role change in the characters and its consequences to the identity deconstruction of fictional subjects